2020
DOI: 10.1051/0004-6361/202038589
|View full text |Cite
|
Sign up to set email alerts
|

Tidal disruption versus planetesimal collisions as possible origins for the dispersing dust cloud around Fomalhaut

Abstract: Recent analysis suggests that the faint optical point source observed around Fomalhaut from 2004–2014 (Fomalhaut b) is gradually fading and expanding, supporting the case that it may be a dispersing dust cloud resulting from the sudden disruption of a planetesimal. These types of disruptions may arise from catastrophic collisions of planetesimals, which are perturbed from their original orbits in the Fomalhaut dust ring by nearby giant planets. However, disruptions can also occur when the planetesimals pass wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…The dissociation timescales of the detected molecules imply that the gas may have been released in a series of events following a disruption of a large planetesimal in the recent past (Cataldi et al 2018). The disruption might have occurred as a result of a collision with another planetesimal (Jackson et al 2014;Lawler et al 2015) or through tidal disruption in a close encounter with a massive planet nested within the disk (Cataldi et al 2018;Janson et al 2020). A large number of fragments of different sizes would have been formed in the disruption, and acquired a range of eccentric orbits with different orbital elements, but which all converge once per orbit to the disruption location where they originally formed.…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation timescales of the detected molecules imply that the gas may have been released in a series of events following a disruption of a large planetesimal in the recent past (Cataldi et al 2018). The disruption might have occurred as a result of a collision with another planetesimal (Jackson et al 2014;Lawler et al 2015) or through tidal disruption in a close encounter with a massive planet nested within the disk (Cataldi et al 2018;Janson et al 2020). A large number of fragments of different sizes would have been formed in the disruption, and acquired a range of eccentric orbits with different orbital elements, but which all converge once per orbit to the disruption location where they originally formed.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy examples include radial-velocity signals of an unclear nature and period in the time series of the nearby K dwarf HD 219134 (Motalebi et al 2015;Vogt et al 2015;Gillon et al 2017), the putative directly imaged planet around Fomalhaut (e.g. Kalas et al 2008;Janson et al 2020;Pearce et al 2021, and references therein), and a number of terrestrial-mass companions tentatively detected inside and outside the temperate zones of nearby M dwarfs, such as GJ 581 (which harbours the most highly debated habitable-zone system, see, Trifonov et al 2018, and references therein), τ Ceti (Tuomi et al 2013b;Feng et al 2017a), GJ 667 C (Delfosse et al 2013;Anglada-Escudé et al 2013;Feroz & Hobson 2014), and HD 40307 (Mayor et al 2009b;Tuomi et al 2013a;Díaz et al 2016).…”
Section: Exoplanetsmentioning
confidence: 99%
“…Such disruptions may happen through direct collisions between planetesimals (Jackson et al 2014;Lawler et al 2015), or, if a massive planet is present in the vicinity, planetesimals can also be tidally disrupted if they pass within the tidal disruption radius of the planet (Cataldi et al 2018). Collisions tend to dominate disruption rates in cases where the parent planetesimals are small, while tidal disruption dominates in cases where the planetesimals are large (Janson et al 2020). Jackson et al (2014) have shown that the collisional breakup of large planetesimals "naturally" produces strongly asymmetric rings, which are made of the small particles produced by the collisional cascade created in the initial breakup's aftermath.…”
Section: Considering Planetesimal Disruption As a Possible Origin For The Ringmentioning
confidence: 99%